Venous Thromboembolism in Hospitalized Melanoma Patients: Analysis from the National Inpatient Sample Database - Alhasson H (Dove Medical Press, 2021)
Hussam Alhasson,1 Kadhim Al-banaa,2 Mohammad Abu-Tineh,3 Bassam Alhasson,4 Yu Zhao,1 Mohamed A Yassin3 1Department of Medicine, Rochester Regional Health, Rochester, NY, USA; 2Department of Hematology, University of California-San Diego, San Diego, CA, USA; 3National Center for Cancer Care and Research, Hamad Medical Corporation, Doha, Qatar; 4Clinical Trials Center of Middle Tennessee, Franklin, Tennessee, USACorrespondence: Mohammad Abu-TinehHamad Medical Corporation, National Center for Cancer Care and Research, HMC, Alrayan Street, Doha, QatarEmail mabutineh@hamad.qaIntroduction: The association between cancer and hyper-coagulability is well known. However, the association between melanoma and venous thromboembolism (VTE) has not been identified.Methods: We studied the national inpatient sample (NIS) which compromise 20% of US hospitalization to better characterize melanoma and VTE. We analyzed the data between 2010 and 2014 using ICD-9 codes.Results: Melanoma patients were grouped into presence/absence of VTE. Multiple logistic regression was used to obtain the odds ratio (OR) to compare the mortality of the inpatient, total charges, length of stay (LOS), and disability at discharge. A total of 61,812 melanoma patients were identified, of which 5.2% were hospitalized for VTE. The presence of VTE was associated with a remarkable higher rate of discharge with a moderate to severe disability (57.5% vs 41.4%, P< 0.001), in-hospital stroke (7.6% vs 4.9%, P< 0.001), and in-hospital mortality (8.8% vs 5.1%, P< 0.001). Costs of hospitalization (64,720$ vs 46,606, P< 0.001) and LOS (5 vs 3 days, P< 0.001) were significantly higher as well in the VTE group. After adjusting for common confounder, VTE was found to be an independent predictor of mortality (OR = 1.596, 95% CI [1.399– 1.821], P< 0.001).Conclusion: In summary, melanoma patients with VTE had higher inpatient mortality, LOS, higher hospital cost, and a higher degree of disability upon discharge.Keywords: melanoma, venous thromboembolism, VTE, coagulation